2001
DOI: 10.1016/s0896-6273(01)00186-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Structured Replay of Awake Hippocampal Ensemble Activity during Rapid Eye Movement Sleep

Abstract: Human dreaming occurs during rapid eye movement (REM) sleep. To investigate the structure of neural activity during REM sleep, we simultaneously recorded the activity of multiple neurons in the rat hippocampus during both sleep and awake behavior. We show that temporally sequenced ensemble firing rate patterns reflecting tens of seconds to minutes of behavioral experience are reproduced during REM episodes at an equivalent timescale. Furthermore, within such REM episodes behavior-dependent modulation of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
770
4
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,006 publications
(809 citation statements)
references
References 35 publications
29
770
4
6
Order By: Relevance
“…Accordingly in humans, post-training modifications of sleep parameters are also observed after conditioning in babies, but only when the stimulus-response association had been successfully learned (Paul and Dittrichova, 1975). At the systems level, experience-dependent replay of neuronal activity during REM sleep has been already demonstrated in animals (Poe et al, 2000;Louie and Wilson, 2001), but not yet proven behaviorally relevant since the link between the performance and the ensuing neural pattern during sleep has never been demonstrated (Peigneux et al, 2001). Here, we provide the first evidence that the strength of rCBF reactivation during post-training REM sleep depends on prior learning level in humans.…”
Section: Does the Level Of Learning Modulate Regional Brain Activitymentioning
confidence: 66%
See 1 more Smart Citation
“…Accordingly in humans, post-training modifications of sleep parameters are also observed after conditioning in babies, but only when the stimulus-response association had been successfully learned (Paul and Dittrichova, 1975). At the systems level, experience-dependent replay of neuronal activity during REM sleep has been already demonstrated in animals (Poe et al, 2000;Louie and Wilson, 2001), but not yet proven behaviorally relevant since the link between the performance and the ensuing neural pattern during sleep has never been demonstrated (Peigneux et al, 2001). Here, we provide the first evidence that the strength of rCBF reactivation during post-training REM sleep depends on prior learning level in humans.…”
Section: Does the Level Of Learning Modulate Regional Brain Activitymentioning
confidence: 66%
“…These processes would thus promote dynamic plastic changes in neuronal populations previously engaged in memory acquisition (Maquet, 2001). Consistently with this hypothesis, several animal studies have shown that neural activity expressed during waking behavior is reinstated during subsequent sleep (e.g., Wilson and McNaughton, 1994;Skaggs and McNaughton, 1996;Qin et al, 1997;Nadasdy et al, 1999;Louie and Wilson, 2001). …”
Section: Introductionmentioning
confidence: 63%
“…The exact beginning and end points were adjusted manually. Using slightly different detection criteria 49 resulted in the definition of similar theta epochs.…”
Section: Analysis Of Network Oscillationsmentioning
confidence: 99%
“…There is also some evidence for replay of representations during REM sleep as well [96,161,164]. Intriguingly, replay of familiar and novel memories occur at different phases of the theta rhythm: novel memories are replayed at the peak of REM-theta, while familiar memories are replayed at the trough [164].…”
Section: A1 Hippocampal Representational Replaymentioning
confidence: 99%